Analysis of Concrete-Filled Steel Tube Reinforced Concrete Column-Steel Reinforced Concrete Beam Plane Frame Structure Subjected to Fire. (8th April 2021) - Bao, Yanhong; Chen, Bowen; Xu, Lei
Abstract : The ABAQUS finite-element analysis platform was used to understand the mechanical behavior of concrete-filled steel tube reinforced concrete (CFSTRC) columns and steel reinforced concrete (SRC) beam plane frames under fire conditions. Thermal parameters and mechanical constitutive model of steel and concrete materials were reasonably selected, the correct boundary conditions were chosen, and a numerical model for the thermal mechanical coupling of CFSTRC columns and SRC beam plane frame structure was established. The finite-element model was verified from related experimental test results. The failure modes, deformation, and internal force distribution of the CFSTRC column and SRC beam plane frames were analyzed under ISO-834 standard fire conditions and with an external load. The influence of beam and column fire-load ratio on the fire resistance of the frame structure was established, and the fire-resistance differences between the plane frame structures and columns were compared. The CFSTRC column-steel reinforced concrete beam plane frame may undergo beam failure or the column and beam may fail simultaneously. The frame structure fire-resistance decreased with an increase of column and beam fire-load ratio. The column and beam fire-load ratio influence the fire resistance of the frames significantly. In this numerical example, the fire resistance of the frames is less than the single columns. It is suggested that the fire resistance of the frame structure should be considered when a fire-resistant structural engineering design is carried out.